Blind Cartography for Side Channel Attacks: Cross-Correlation Cartography. (5th April 2012) - Sauvage, Laurent; Guilley, Sylvain; Flament, Florent; Danger, Jean-Luc; Mathieu, Yves
Abstract : Side channel and fault injection attacks are major threats to cryptographic applications of embedded systems. Best performances for these attacks are achieved by focusing sensors or injectors on the sensible parts of the application, by means of dedicated methods to localise them. Few methods have been proposed in the past, and all of them aim at pinpointing the cryptoprocessor. However it could be interesting to exploit the activity of other parts of the application, in order to increase the attack's efficiency or to bypass its countermeasures. In this paper, we present a localisation method based on cross-correlation, which issues a list of areas of interest within the attacked device. It realizes an exhaustive analysis, since it may localise any module of the device, and not only those which perform cryptographic operations. Moreover, it also does not require a preliminary knowledge about the implementation, whereas some previous cartography methods require that the attacker could choose the cryptoprocessor inputs, which is not always possible. The method is experimentally validated using observations of the electromagnetic near field distribution over a Xilinx Virtex 5 FPGA. The matching between areas of interest and the application layout in the FPGA floorplan is confirmed by correlation analysis.